Molecularly Imprinted Membrane Possessing Selectivity and Adsorption Behaviour to Targeted (-)-Epigallocatechin-3-gallate Molecule - Zhang, Haihui; Qin, Yu; Duan, Yuqing; Xu, Feifei; Zhang, Can; Yan, Yongsheng; Ma, Haile; Wang, Yanhong (Asian Journal of Chemistry, 2013)
An efficient molecular imprinted membrane (MIM) was prepared and successfully used for selective absorbing (-)-epigallocatechin-3-gallate (EGCG) from the solution of tea. The MIM obtained was characterized by FT-IR and scanning electron microscopy. Kinetics, binding and selectivity experiment were used to study the adsorption properties of MIM in EGCG solution. The results showed that the template molecule had been incorporated into the support membrane by physical measure, the kinetics of MIM followed the pseudo-second-order kinetic model and the process of equilibrium adsorption could be simulated by Langmuir model. Molecular imprinted membrane exhibited better selectivity for EGCG from the extract of tea polyphenol than non-molecularly imprinted membrane (NIM) and the relative selectivity coefficients of MIM for EGCG/(-)-epigallocatechin, EGCG/(+)-catechin, EGCG/(-)-gallocatechin gallate and EGCG/(-)-epicatechin-3-gallate were 3.22, 1.34, 1.33 and 1.59, respectively. These findings indicated that the MIM had a good selectivity and could be used to separate EGCG from the real sample.